Profile and Employability Performance of Jose Rizal Memorial State University - Tampilisan Campus Bachelor of Elementary Education Graduates - Napallaton, Marife; Baquiller, Gemarie (JPAIR Institutional Research, 2017)
Nowadays, academic institutions need to make an assessment of their graduates to introduce improvements of the program. The study aimed to trace the BEEd graduates S.Y. 2010 - 2013 based on their profile and employability performance. The study utilized a descriptive - survey research design to collect data using the documents of records and files of the education graduates for School Year 2010-2013. The researchers used frequency count and simple percentage to answer the problems. The study revealed that most of the graduates are employed in the different public and private agencies. The graduates were almost equally distributed in terms of performance rating since there are outstanding, very satisfactory and satisfactory. The study concludes that most of the BEEd graduates from S.Y. 2010 - 2013 are already employed. There are more females who are employed in public and private agencies compared to males. Most of the graduates are regular in their jobs. As to their nature of work, there are more very satisfactory in terms of job performance rating. Therefore, parents may also be encouraged to send their children to school and enroll education even if they are male or female because they are still employable. The school may take possible measures or intervention for linkages so that they could help their graduates get employment.
Keywords: Tracer Study; employability performance; BEEd graduates; descriptive design; Philippines